2005
DOI: 10.1128/jcm.43.12.5983-5991.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 43 Streptococcus Species by Pyrosequencing Analysis of the rnpB Gene

Abstract: Pyrosequencing technology was evaluated for identification of species within the Streptococcus genus. Two variable regions in the rnpB gene, which encodes the RNA subunit of endonuclease P, were sequenced in two reactions. Of 43 species, all could be identified to the species level except strains of the species pairs Streptococcus anginosus/S. constellatus and S. infantis/S. peroris. A total of 113 blood culture isolates were identified by pyrosequencing analysis of partial rnpB sequences. All but eight isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 46 publications
1
47
1
1
Order By: Relevance
“…variability within the 23S rRNA gene targets did not provide species-level identification for all bacteria, it did provide genus-level identification for most other organisms associated with bloodstream infection. Certain highly related bacteria, e.g., S. pneumoniae and S. mitis, or Enterobacter species and C. freundii were not differentiated using this target; DNA targets outside of the rRNA genes will most likely be needed for this purpose (3,9,10,20,21,25). The overall agreement between pyrosequencing and culturebased identification methods was high (97.8% [264/270]).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…variability within the 23S rRNA gene targets did not provide species-level identification for all bacteria, it did provide genus-level identification for most other organisms associated with bloodstream infection. Certain highly related bacteria, e.g., S. pneumoniae and S. mitis, or Enterobacter species and C. freundii were not differentiated using this target; DNA targets outside of the rRNA genes will most likely be needed for this purpose (3,9,10,20,21,25). The overall agreement between pyrosequencing and culturebased identification methods was high (97.8% [264/270]).…”
Section: Discussionmentioning
confidence: 92%
“…Turenne et al used single-stranded conformation polymorphism analysis of PCR amplicons to distinguish between organisms (23), while Peters et al used fluorescence in situ hybridization to identify pathogens out of positive blood cultures (19). Several investigators have used pyrosequencing (Biotage, Uppsala, Sweden) to identify numerous bacteria, yeasts, and fungi (9)(10)(11).…”
mentioning
confidence: 99%
“…However, it involves more inputs and selection of other genes out of a few thousand genes within the genome is not an easy task. In spite of the fact that around 23 genes have been used frequently in many studies carried out for identifying Streptococcus, no consensus gene has been identified [3,4,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It has also not been realized that except recA, the rest of the 22 genes are not present in all the species of Streptococcus.…”
Section: Discussionmentioning
confidence: 99%
“…Although, multilocus sequence analysis (MLSA) has been relatively quite successful in the identification of a wide range of bacterial species [33], however, using sequences of 7 HKGs: guaA, map, pfl, ppaC, pyk, rpoB, and sodA, also did not prove suitable for rapid identification of Streptococcus species [21]. MLSA using gdh, ddl along with guaA, map, pfl, ppaC, pyk, rnpB, rpoB, sodA, and tuf have been useful in identifying Streptococcus species [32,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…All sequences of the dominant bands could be identified to the species level except for the species pairs of S. mitis/pneumoniae and S. infantis/peroris. The inability of our assay to distinguish these two pairs of species may due to a high level of similarity between them, making identification of some genotypes of these species difficult solely on the basis of the rnpB gene (Innings et al, 2005;Täpp et al, 2003).…”
Section: Oral Streptococci Succession Associated With S-eccmentioning
confidence: 99%